HUBUNGAN KEKERABATAN AKSESI PISANG KEPOK (Musa paradisiaca Formatypica) DI KABUPATEN MUNA BERDASARKAN KARAKTER MORFOLOGI DAN PENANDA RAPD - Wijayanto, Teguh; Boer, Dirvamena; Ente, La (Jurnal Agroteknos, 2013)
Twenty-four accessions that belong to four groups of kepok banana in Muna Regency have been analyzed for their genetic diversity based on morphological characters (qualitative and quantitative characters), and a few accessions based on RAPD markers. This study aimed to determine the genetic diversity and phylogenetic relationship of accessions of kepok bananas based on 52 qualitative and 12 quantitative morphological characteristics and DNA characteristics. Results of clustering analysis showed the euclidian values ranged between 0.50 to 1.00 for the qualitative data, 0.01 to 0.50 for quantitative data, and 0.83 to 0.88 for DNA profile data. Combined qualitative and quantitative data had similarity coefficient ranged from 0.00 to 2.50. Dendogram of each character produced 2 main groups. The main group 1 formed subgroups. Although the qualitative and quantitative characters resulted in different accession groupings, the combined data analysis of quantitative and qualitative data showed that kepok banana in Muna regency was classified into 4 sub groups namely banana Manuru, Bugisi, Jiwaka and Manuru Lakabu. Keywords: cluster analysis, kepok banana, qualitative and quantitative characters, morphology, RAPD markers.